The effect of Selacid® on the performance and health status of growing and finishing rabbit - Heincinger, Mónika; Abayné Hamar, Enikő; Balláné Erdélyi, Márta; Fazekas, Natasa; Kovács-Weber, Mária; Kustos, Károly; Zimborán, Ágnes; Nyíri, András; Szabó, Rubina Tünde; Gerber, Zsuzsanna; Gerber, Johann; Somodi, Brigitta (Animal welfare, Ethology and Housing Systems (AWETH), 2016)
The use of organic acids in the feed industry dates back a long time, but while they were used to preserve feed, nowadays they are used as a performance enhancer. In our experiments, rabbits consumed 10% and 20% of Selacid® in their feed during their 5-11 week growing phase. Our conclusion was that Selacid®-containing feed has a beneficial effect on weight gain, regarding the live weight of rabbits. Mortality remained low in all groups, but among the Selacid® treated groups, the mortality rate was even lower, than in the control’s results.
Keywords: organic acid; growth; mortality